2021
DOI: 10.1002/chem.202103122
|View full text |Cite|
|
Sign up to set email alerts
|

Thiophene‐Fused 1,4‐Diazapentalene: A Stable C=N‐Containing π‐Conjugated System with Restored Antiaromaticity

Abstract: A thiophene-fused 1,4-diazapentalene (TAP) was rationally designed and synthesized as a C=N-containing 4n π-electron system that exhibits restored antiaromaticity impaired by the doping with C=N bonds. X-ray crystallographic analysis and quantum chemical calculations revealed that the annulation of thiophene rings with the 1,4diazapentalene moiety resulted in a much higher antiaromaticity than the pristine 1,4-diazapentalene. These effects can be ascribed to the reduced bond alternation of the eightmembered-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 96 publications
0
20
0
Order By: Relevance
“…Replacing nitrogen atoms with carbons causes an increase in HOMO energy. 29 It should be noted that a wavefunction node, where the wavefunction is zero and changes signs, was found on a single C-C bond connecting DHPP units in the tetramer (Fig. S3, ESI †).…”
Section: Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Replacing nitrogen atoms with carbons causes an increase in HOMO energy. 29 It should be noted that a wavefunction node, where the wavefunction is zero and changes signs, was found on a single C-C bond connecting DHPP units in the tetramer (Fig. S3, ESI †).…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…28 Doping antiaromatic hydrocarbons with nitrogen leads to an increase in their electron-withdrawing ability. 29,30 In this work, we report a theoretical study of aromaticity, electronic and photoinduced electron transfer (PET) properties of the complexes based on C 60 fullerene with nanohoops built from benzene-fused antiaromatic pyrrolo [3,2-b]pyrrole (PP) and its aromatic analog 1,4-dihydropyrrolo [3,2-b]pyrrole (DHPP). The structural units have already been synthesized and characterized, 31,32 whereas the nanohoops were modeled based on the similarity to [4]CDBP .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we investigated the redox interconversion of 9 , which possesses two oxidizable NH groups (Figure 4). The screening of various oxidizing agents revealed that NiO 2 [5f,16] provided the optimum results in terms of reaction efficiency and reproducibility. After the treatment of 9 with NiO 2 , chromatographic purification provided the corresponding oxidized form 11 in 86 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…[95] formed 105, which rapidly dimerized only to 106 b (2) deprotonation and CuCl 2 mediated oxidative coupling affording both 106 a and 106 b. Subsequent photolysis of the dimers in a frozen argon matrix afforded the free parent pentalene (105). IR data suggests that pentalene has highly localized single and double bonds, a characteristic of antiaromatic species.…”
Section: Pentalenementioning
confidence: 99%
“…NICS values confirmed that the pentalene centers between the phenanthrene fused molecules were more antiaromatic than dibenzopentalene; furthermore, the computational data suggested that there was a linear correlation between the localized aromaticities within the phenanthrene fusions and the antiaromaticity of the pentalene core. While there has been work on tuning the antiaromaticty by “doping” the pentalene core directly via the installation of nitrogen atoms within the pentalene core, [105] Oshima's work suggests a rational way of tuning the antiaromaticity of the native pentalene core by judicious use of ring fusion.…”
Section: Pentalenementioning
confidence: 99%